Design of Microwave Antenna Array for Imaging of Multiphase Flows in Polypropylene Pipes - Khaldoun Alkhalifeh; Hatem Rmili; Bandar Hakim; Nebras Sobahi; Youssef AL-Turki (International Journal of Antennas and Propagation)
The oil and gas industry requires accurate sensors to control fluid flow in pipelines during the production process from horizontal and near horizontal wells. The extracted crude oil is usually a multiphase mixture of oil, water, and gas, and the accurate measurement of the ratio of each multiphase within the pipeline is an important parameter to manage wells efficiently by maximizing the hydrocarbons that can be extracted. Various methods have been developed for determining the phase ratio including mechanical, optical, X-ray or gamma ray, ultrasound, nuclear magnetic resonance (NMR), and rarely microwave techniques. However, these methods do not permit the knowledge of the real-time evolution of the phase ratio and are less precise. Here, we propose and develop by simulation two microwave systems, in horizontal and vertical polarizations, to choose the optimal configuration for crude pipeline imaging applications. First, the pipeline containing crude oil was modeled and its thermal and dielectric properties are proposed. Then, the antennas array performances were optimized and assembled to the pipeline. Different numbers of antenna elements were successfully investigated using CST simulation in both vertical and horizontal polarizations to find the optimal number of antenna elements for the pipeline applications.